Fuzzy Mamdani DSS for STIKOM Student Boarding House Selection - Batubara, Ela Roza; Poningsih, Poningsih; Siadari, Nina Helnida; Sidauruk, Nadia (Universitas Islam Sumatera Utara, 2026)
A Decision Support System (DSS) is a system designed to assist users in decision-making based on valid data, involving multiple criteria within a short timeframe. This study employs the Fuzzy Mamdani method as the data processing formula for selecting boarding houses for STIKOM Tunas Bangsa Pematangsiantar students. Selecting a boarding house is a crucial decision faced by migrant students, involving subjective criteria such as price, distance, facilities, room size, and security. Without a systematic tool, students may struggle to choose boarding houses that best suit their preferences, potentially leading to dissatisfaction. This research aims to design and implement a DSS using the Fuzzy Mamdani method to assist students in boarding house selection. The method was chosen for its ability to accommodate linguistic and ambiguous criteria, transforming them into objective and measurable decisions. Five input variables were used: price (Rp 500,000-2,000,000), distance (0-5 km), facilities (0-100), room size (4-30 m²), and security (0-100), with feasibility (0-100) as output. Fuzzy sets and membership functions were defined for each variable, and 45 IF-THEN rules were constructed. Manual calculation for Kost Bio (price Rp 250,000, distance 2.2 km, facilities 88, room size 20.16 m², security 0) produced a feasibility score of 85 (Very Feasible), close to the expert assessment of 93. The system successfully provides objective recommendations, helping students make informed boarding house choices efficiently.